Identification of Transcription Factor Genes and Functional Characterization of PlMYB1 From Pueraria lobata - Shen, Guoan; Wu, Ranran; Xia, Yaying; Pang, Yongzhen (Frontiers in Plant Science, 2021)
Kudzu, Pueraria lobata, is a traditional Chinese food and medicinal herb that has been commonly used since ancient times. Kudzu roots are rich sources of isoflavonoids, e.g., puerarin, with beneficial effects on human health. To gain global information on the isoflavonoid biosynthetic regulation network in kudzu, de novo transcriptome sequencings were performed using two genotypes of kudzu with and without puerarin accumulation in roots. RNAseq data showed that the genes of the isoflavonoid biosynthetic pathway were significantly represented in the upregulated genes in the kudzu with puerarin. To discover regulatory genes, 105, 112, and 143 genes encoding MYB, bHLH, and WD40 transcription regulators were identified and classified, respectively. Among them, three MYB, four bHLHs, and one WD40 gene were found to be highly identical to their orthologs involved in flavonoid biosynthesis in other plants. Notably, the expression profiles of PlMYB1, PlHLH3-4, and PlWD40-1 genes were closely correlated with isoflavonoid accumulation profiles in different tissues and cell cultures of kudzu. Over-expression of PlMYB1 in Arabidopsis thaliana significantly increased the accumulation of anthocyanins in leaves and proanthocyanidins in seeds, by activating AtDFR, AtANR, and AtANS genes. Our study provided valuable comparative transcriptome information for further identification of regulatory or structural genes involved in the isoflavonoid pathway in P. lobata, as well as for bioengineering of bioactive isoflavonoid compounds.